Analysis and modeling of indicators of sustainable development of regions in the Republic of Kazakhstan - Yemelina, N.K.; Assanova, M.A.; Sitenko, D.A. (BUKETOV BUSINESS REVIEW, 2017)
Sustainable development management includes three major components: environmental, social, economic. This paper is focused mainly on environmental part.The article includeseconometric modeling approach in the analysis of environmental governance in the Republic of Kazakhstan on the way to sustainable development. We estimate regions in the Republic of Kazakhstan according to their economic and environmental development. Based on the above-mentioned we proposed 4 clusters. According to the analysis of environmental situation we found out that there is a need to minimize ecological consequences, future externalities for new generations. Public authorities need to understand it in the process of implementation of long-term social and economic strategy in the Republic of Kazakhstan. The prediction of the transition to «sustainable» development made by our macroeconomic model is very favourable for the Republic of Kazakhstan from economic, environmental and social points of view. In our model, it was shown that «sustainable development» not only leads to the economic development of the country as a whole, but also provides a higher GRP growth rate, smoothes uneven regional progress, and guarantees «development» itself - one of the key indicators of the country’s well-being.